Viamigo: Monitoring Tool to Support Independent Travel by Persons with Intellectual Disabilities. Issue 1 (2017) - Neven, An; Vanrompay, Yves; Declercq, Katrien; Janssens, Davy; Wets, Geert; Dekelver, Jan; Daems, Jo; Bellemans, Tom
Persons with intellectual disabilities (PwIDs) often aspire to more social inclusion by engaging in more community activities but encounter social barriers when traveling independently. Therefore, PwIDs are often accompanied by family members, friends, or volunteers. In order to both support the independent outdoor mobility of PwIDs themselves and reduce the caregivers' burden, the geographic information system–based application "Viamigo" was developed (www.viamigo.be ), which allows a personal coach to monitor an individual in real time from a distance. The goal is to teach PwIDs a known individual route that they can accomplish independently while being monitored by a personal coach, caregiver, family member, or friend who is taking care of the individual making the trip. Viamigo determines the location of the user and compares this in time and space within a predetermined range and automatically sends notifications to the coach in case the user deviates from the route, travels at an incorrect speed, or enters or leaves a safe or dangerous zone, among other factors. Besides this on-route functionality, Viamigo also allows the creation of geofences around destinations (to monitor whether the user stays within a predefined zone) and emergency tracking. The initial results are promising: PwIDs successfully used Viamigo for a heterogeneous set of trips performed by several travel modes (bus, cycling, and walking) for several activity purposes (both daily recurrent trips to the day center and trips for shopping, social, and recreational purposes) and for different distances.